(untitled) (Bangladesh Journal of Agricultural Research, 2008)
An experiment was carried out during October 1999 to January 2000 in the field of Horticulture Department of Bangladesh Agricultural University, Mymensingh with two chilli accessions viz, C-0277 and C-0272 of moisture stress tolerant and susceptible type. The chilli accessions were put into trial under field condition to observe the effects of different water treatments imposed at their vegetative, flowering, and fruiting stages of growth and development. Results of the experiment revealed that accession C-0277 was water stress tolerant compared to accession C-0272. Watering at 4-day interval significantly gave the highest yield and dry matter. While, watering imposed in fruiting stage produced the maximum yield and dry matter in chilli. Key Words: Chilli accessions, field condition, water stress, yield. doi:10.3329/bjar.v33i3.1594 Bangladesh J. Agril. Res. 33(3) : 353-362, September 2008